Revolusi Gaya Belajar untuk Fungsi Otak - Waluyo, M. Edy (NADWA, 2014)
This paper elaborate on an attempt to maximize the function of brain as a form of learning revolution. Learn properly is not an issue of whether or not a student pass the test. The meaning of learn is broader than a success of passing the ex-ams. This is certainly related to the fun learning during the process of maximiz-ing the ability to achieve success. Each student has a different learning styles depending on his/her character. There are four different models of learning that has been known today, ie sketch, sound, tactics, and movement. Students who have studied the model using the sketch tends to be easier to understand the in-formation that they see. While those who have learned how to use the sound tends to be easier to capture verbal information from the teacher. Students who have a tendency to learn with tactics models require a touch of emotion. The kinesthetic learning models require movement in the learning process so that children learn more successfully.Keyword: learning, model of learning, successful learning